China with a Cut : Globalisation, Urban Youth and Popular Music - Kloet, Jeroen de (Book collections on Project MUSE., 2010)
In the wake of intense globalisation and commercialisation in the 1990s, China saw the emergence of a vibrant popular culture. Drawing on sixteen years of research, Jeroen de Kloet explores the popular music industry in Beijing, Hong Kong and Shanghai, providing a fascinating history of its emergence and extensive audience analysis, while also exploring the effect of censorship on the music scene in China. China with a Cut pays particular attention to the dakou culture: so named after a cut nicked into the edge to render them unsellable, these illegally imported Western CDs still play most of the tracks. They also played a crucial role in the emergence of the new music and youth culture. De Kloet's impressive study demonstrates how the young Chinese cope with the rapid economic and social changes in a period of intense globalisation, and offers a unique insight into the socio-cultural and political transformations of a rising global power.